Students’ Errors Analysis in Finishing A Problem Solving Test Based on Newman Procedures in Trigonometry Materials - Nandika Sri Wahyuni; Evi Widayanti (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to describe the types of student errors in solving problems based on the Newman procedure, the causes of errors and solutions to resolve errors made by students in solving problems on Trigonometry material. In this study using qualitative methods. The instruments in this study were tests and interviews. The results of the research are written test data and information from interviews, and the results of the analysis of researchers obtained several conclusions. Mistakes made by students in completing problem-solving test questions on Trigonometry material ie students cannot receive information from the questions properly, students can model through sketch drawings but the information on the sketch does not match the problems in the questions, students are not able to choose what method or formula used to solve problems and lack of understanding of the method or formula chosen, students do not use all the information provided on the problem, as a result of previous mistakes, when the initial process is wrong the final result must be wrong and students are not used to writing conclusions at the end of the work question.